Syzygium anamalaianum (Myrtaceae), a new tree species from the Western Ghats of Tamil Nadu, India - Ramasubbu, Raju; Surendran, Anjana; Kasi, Karuppa Samy (Phytotaxa, 2020)
Syzygium anamalaianum, a new species from Anamalai Tiger Reserve, Tamil Nadu, India is described. This species is closely allied to Syzygium bharathii and S.caryophyllatum, but differs from it by having thick elliptic or ovate–lanceolate leaves with deeply grooved midrib, 4–angled prominently winged peduncle, smaller flower, funnel or pyriform hypanthium, inwardly curved stamens of varying lengths and obovate or subglobular seeds. This combination of characters makes determining the relationships of Syzygium anamalaianum difficult.